Development of Air Defence in the United States between 1917 and 1945 - Radomyski, Adam (Historia i Polityka, 2023)
The article presents the results of academic research focusing on the origins and development of anti-aircraft artillery in the United States which was to guarantee the safety of American soldiers fighting in the First and Second World Wars. The findings of this study confirm that, in the early days, knowledge of the phenomena occurring in the air dimension of armed struggle was primarily empirical. As early as 1916, Alexander Graham Bell warned of the possibility of air raids on the United States. Over the next 25 years, experts conducted research into air defence, which became crucial in its subsequent development. The basis for the development of air defence was the emergence of a new weapon at the end of the First World War, i.e., anti-aircraft artillery. Basing on the experience of the United States from the First World War in the interwar period, air defence began to be seen in terms of a system whose main task was to detect and destroy enemy aviation, attacking troops, civilians and facilities at the rear of the front. Considering the outlined problem scenario and the subject of the research, it was assumed that the aim of the article will be to discuss the stages of the development of air defence in the United States in the years 1917–1945 and the experience of US anti-aircraft artillery gained on the fronts of the First and Second World Wars.